Metabolic pathways for microalgal biohydrogen production: Current progress and future prospectives. (December 2020) - El-Dalatony, Marwa M.; Zheng, Yuanzhang; Ji, Min-Kyu; Li, Xiangkai; Salama, El-Sayed
Graphical abstract: Highlights: Clear differentiation among all the metabolic pathways of microalgal Bio-H2 . Microbial electrolysis cells (MEC) is a new approach for microalgal Bio-H2 . Report the challenges (operation cost & economic feasibility) of microalgal Bio-H2 . Multistage photobioreactors improved microalgal Bio-H2 . Genetic engineering & synthetic biology enhanced the microalgal Bio-H2 . Abstract: Microalgal biohydrogen (bioH2 ) has attracted global interest owing to its potential carbon-free source of sustainable renewable energy. Most of previous reviews which focused on microalgal bioH2, have shown unclear differentiation among the metabolic pathways. In this review, investigation of all different metabolic pathways for microalgal bioH2 production along with discussion on the recent research work of last 5-years have been considered. The major factors (such as light, vital nutrients, microalgal cell density, and substrate bioavailability) are highlighted. Moreover, effect of various pretreatment approaches on the constituent's bioaccessibility is reported. Microbial electrolysis cells as a new strategy for bioH2 production is stated. Comparison between the operation conditions of various bioreactors and economic feasibility is also emphasized. Genetic, metabolic engineering, and synthetic biology as recent technologies improved the microalgal bioH2 production through inactivation of uptake hydrogenase (H2 ase), inhibition of the competing pathways in polysaccharide synthesis, and improving the O2 tolerant H2 ase.